Numerical and experimental investigation of Johnson–Cook material models for aluminum (Al 6061-T6) alloy using orthogonal machining approach - Akram, Sohail; Jaffery, Syed Husain Imran; Khan, Mushtaq; Fahad, Muhammad; Mubashar, Aamir; Ali, Liaqat (Advances in mechanical engineering, 2018)
This research focuses on the study of the effects of processing conditions on the Johnson–Cook material model parameters for orthogonal machining of aluminum (Al 6061-T6) alloy. Two sets of parameters of Johnson–Cook material model describing material behavior of Al 6061-T6 were investigated by comparing cutting forces and chip morphology. A two-dimensional finite element model was developed and validated with the experimental results published literature. Cutting tests were conducted at low-, medium-, and high-speed cutting speeds. Chip formation and cutting forces were compared with the numerical model. A novel technique of cutting force measurement using power meter was also validated. It was found that the cutting forces decrease at higher cutting speeds as compared to the low and medium cutting speeds. The poor prediction of cutting forces by Johnson–Cook model at higher cutting speeds and feed rates showed the existence of a material behavior that does not exist at lower or medium cutting speeds. Two factors were considered responsible for the change in cutting forces at higher cutting speeds: change in coefficient of friction and thermal softening. The results obtained through numerical investigations after incorporated changes in coefficient of friction showed a good agreement with the experimental results.